Computational study on the panel size effects of the compressive load-bearing capacity after impact of laminated composites. (1st March 2023) - Lin, Shiyao; Ranatunga, Vipul; Waas, Anthony M.
Abstract: Computational results on the panel size effect in the compression after impact (CAI) deformation and damage are presented in this paper. The experimental counterpart of this paper is Lin et al. (2022). The in-plane sizes studied are 152.4 mm × 101.6 mm, 177.8 mm × 177.8 mm, and 330.2 mm × 330.2 mm. The thicknesses studied are 24-ply (3.1 mm) and 48-ply (6.2 mm). The two stacking sequences are [45/-45/0/90/0/0]ns and [45/0/-45/90]ns . The material system studied is IM7/977-3. Enhanced Schapery Theory with 2D plane stress states (2D EST) have been used for the progressive failure analyses. Predicted LVI-induced damage was transferred onto the CAI mesh based on a damage transferring algorithm. The results show that 2D EST can successfully capture the deformation and CAI-induced damage patterns of the panels with various sizes. With detailed computational results, different mechanisms for the CAI failure have been analyzed and categorized. A more rigorous and practical term — compressive load-bearing capacity after impact (CLBCAI) has been proposed to replace compressive strength after impact (CSAI) to account for the effects of impact damage and panel geometry. This paper provides results to show that the existing industrial standard D7137 (2017) is limited and may need to be replaced. Highlights: Study performed on panel size effects on Compressive Load bearing capacity of composite laminates. A predictive numerical framework is developed and results compared against experiments. The model captured the observed effects with full failure sequences. A 3D-EST model (extension) development is suggested for future work.